Basic guide to system safety - Vincoli, Jeffrey W. (Wiley, 2014)
"This book provides guidance on including prevention through design concepts within an occupational safety and health management system. Through the application of these concepts, decisions pertaining to occupational hazards and risks can be incorporated into the process of design and redesign of work premises, tools, equipment, machinery, substances, and work processes including their construction, manufacture, use, maintenance, and ultimate disposal or reuse. These techniques provide guidance for a life-cycle assessment and design model that balances environmental and occupational safety and health goals over the life span of a facility, process, or product.The new edition is expanded to include primer information on the use of safety assurance techniques in design and construction"...Provided by publisher